Global prevalence of obesity in the older adults: A meta-analysis - Ali Asghar Khaleghi; Nader Salari; Niloofar Darvishi; Shadi Bokaee; Samira Jafari; Mahvan Hemmati; Masoud Mohammadi (Public Health in Practice)
Objective: Obesity is a chronic and complex disease defined as the excessive accumulation of body fat and is one of the leading public health problems in developed and developing countries. Due to the importance of obesity, this study was conducted to investigate the prevalence of obesity in the older adults. Study design: meta-analysis. Methods: In this study, systematic review and meta-analysis of study data on the prevalence of obesity in the older adults in the world using keywords including: prevalence, outbreak, Body Mass Index, BMI, obesity, Elderly, aged, older adult, in Science Direct databases, Scopus, PubMed, Web of Science, Iran Doc, Mag Iran, SID and Google Scholar search engine were extracted without time limit until August 2020. The target population under study is the world's elderly, and obesity means a BMI≥30. The Random Effects Model was used to perform the analysis and, Comprehensive Meta-Analysis Software version 2.0 was used for data analysis. Results: In review 44 studies with a total sample size of 45,745,944 prevalence of obesity in the older adults of the world; In a meta-analysis of 25.3 % (95 % CI: 21.9–29). It was found that the highest prevalence of obesity in the older adults in South America with 40.4 % (95 % CI: 12.5–76.4). In addition, continental Europe with 33.6 % (95 % confidence interval: 24.1–44.5). The meta-regression results showed an increasing trend in the prevalence of obesity in the older adults in the world with an increasing sample size and a decreasing trend with increasing the study (P < 0.05). Conclusion: Given that the prevalence of obesity in the older adults is high, health policymakers must take adequate measures to increase public awareness about the risks of obesity in the older adults.